2004
DOI: 10.1016/s1074-7613(04)00072-x
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 Utilizes an Alternative Receptor to Drive Apoptosis of Th1 Cells and Skews Neonatal Immunity toward Th2

Abstract: Primary neonatal Th1 cells develop alongside of Th2 upon priming of the newborn but undergo apoptosis upon recall with antigen. These Th1 cells were isolated, and their death was correlated with elevated IL-13Ralpha1 chain expression. Strikingly, neutralization of Th2s' IL-4 reduced apoptosis, sustained recall responses, and the live Th1 cells displayed a decrease in IL-13Ralpha1 expression. Blockade of IL-13Ralpha1 or IL-4Ralpha also restores recall and secondary Th1 responses. Adult T cells primed within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
164
2
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(181 citation statements)
references
References 34 publications
9
164
2
6
Order By: Relevance
“…Newborns are especially prone to infections for which cell-mediated immunity is protective (1,3). Neonates and infants also have a reduced or suboptimal capacity to mount an effective cell-mediated immunity in response to most vaccines (1,(3)(4)(5). However, introducing a vaccine Ag into the cytoplasm of APCs induces a significant CD8 CTL response even in neonates (3,6,7).…”
Section: Induction Of Protective Immunity Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Newborns are especially prone to infections for which cell-mediated immunity is protective (1,3). Neonates and infants also have a reduced or suboptimal capacity to mount an effective cell-mediated immunity in response to most vaccines (1,(3)(4)(5). However, introducing a vaccine Ag into the cytoplasm of APCs induces a significant CD8 CTL response even in neonates (3,6,7).…”
Section: Induction Of Protective Immunity Tomentioning
confidence: 99%
“…However, introducing a vaccine Ag into the cytoplasm of APCs induces a significant CD8 CTL response even in neonates (3,6,7). Contrary to the induction of CTLs, Th1 (IFN-␥ producing) CD4 T cell responses have not only been difficult to induce in the neonate, but appear even more difficult to sustain (4,5,8,9).…”
Section: Induction Of Protective Immunity Tomentioning
confidence: 99%
“…Th2 cell immunity suppresses alloresponses during pregnancy and promotes growth of the placenta (Fock et al, 2013;Forsthuber et al, 1996). The enhanced Th2 cell bias of neonatal T cells is in part T cell intrinsic and transient (Li et al, 2004;Sornasse et al, 1996;White et al, 2002), but cord blood DCs have also been shown to lack production of the Th1-cell-polarizing cytokine IL-12p70 (Goriely et al, 2001;Upham et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has therefore been proposed that humans are born with a "type 2 immune bias", the reason of which remains to be established [42]. is bias is thought to be counteracted through the induction of 1, 17 or Tregs a er colonization with a symbiotic microbiota.…”
Section: Microbiota and Type 2 Immune Responsesmentioning
confidence: 99%